Transforming from victim to survivor—Part 1: Strategies for clinicians to safeguard themselves, colleagues, and patients from disruptive intraoperative behaviour - Villafranca, Alexander; Adams, Brett; Krestow, Owen; Forest, Alison; Yasinski, Lesia (Operating Room Nurses Association of Canada Journal, 2025)
Disruptive intraoperative behaviour is pervasive and harms clinicians, patients, and institutions. Clinicians exposed to disruptive behaviour inadvertently become parties to an interpersonal conflict. While previous reviews focused on antecedents and consequences of disruptive behaviour, we adopt a conflict resolution perspective to (1) equip clinicians to maintain their well-being when faced with disruptive behaviour; and (2) outline how clinicians can respond to prevent escalation while not reinforcing the behaviour. Clinician responses start with cognitive appraisals, which determine the psychological impact of disruptive behaviour. Clinicians can improve their appraisals using situational awareness, cognitive reappraisal, and grounding techniques. Over the long term, clinicians can use adaptive coping mechanisms, characterized by a “survivor” mindset, and avoid maladaptive strategies, characterized by a psychologically harmful “victim” mindset. Clinicians must be mindful of the roles they assume in conflicts. Manipulative and malicious responses turn clinicians into accomplices or retaliatory offenders, while overusing passive responses risks relegating them to being enabling bystanders. Instead, clinicians should respond assertively, which transforms them into upstanders. Successful assertive efforts involve refocusing attention, avoiding flash escalation, using structured communication tools, setting clear boundaries, and practising these skills via simulation. By adopting these micro-level interventions, clinicians can help cultivate a respectful OR culture and safeguard their well-being.